Backsliding in gender equality: a reminder that progress is a constant struggle. (14th October 2022) - Clark, Jocalyn; Dhatt, Roopa
Abstract : Ensuring women's equal participation in policy and decision making is essential if we are to tackle the global crises we face, say Jocalyn Clark and Roopa Dhatt